Peningkatan Kompetensi Masyarakat Melalui Inovasi Pemanfaatan Labu Kuning Menjadi Makanan Kreatif Dan Sehat - Siswanto Pabidang; Selasih PutriIsnawati Hadi; Ade Elvina; Dian Ekawati Putri; Helen Puspa Sari; Tri Iriyani; Angela Lovindra Nainggalis (J.Abdimas: Community Health, 2020)
The people of Kopeng Hamlet, Cangkringan District, Sleman Regency have natural wealth in the form of yellow squash (CucurbitaMoschata). This community service activity aims to increase public knowledge about the nutritional content of pumpkin and how to process pumpkin to become creative and healthy food. Because so far the natural resources of pumpkin that are very abundant in Kopeng Hamlet have not been maximally used as creative food and of high nutritional value. The methods used are interviews, focus group discussions (FGD) and practice. The results of this activity showed that the women who joined the PKK group were very enthusiastic about understanding the nutritional content of pumpkin which is commonly found in Kopeng Hamlet and very actively participating in the practice of processing food made from pumpkin. This activity has been successfully implemented thanks to the active participation of the whole community.